The efficacy and safety of remimazolam besylate, ciprofol, and propofol during hysteroscopy - Shan, Weifeng; Gao, Shuying; Ai, Mengting; Lan, Haiyan; Duan, Gongchen; Dong, Xiaoli; Xu, Qiaomin; Wu, Yini; Wu, Jimin (Frontiers in Pharmacology, 2025)
ObjectiveRemimazolam besylate and Ciprofol are newer sedatives used in minor surgeries. Propofol is a classic drug mainly used for short surgeries. This trial was conducted to compare the efficacy and safety of remimazolam besylate, ciprofol, and propofol during hysteroscopic surgeries.MethodsPatients undergoing hysteroscopy were randomly assigned to receive remimazolam besylate (Group R), ciprofol (Group C), or propofol (Group P). A total of 194 patients were assessed for eligibility. One patient in Group P was excluded because the operation had timed out of 60 min. Patients all in Group R、Group C and Group P received an induction dose of 0.2 mg/kg remimazolam besylate、0.4 mg/kg ciprofol、2.0 mg/kg propofol seperately over 30 s. A corresponding dosage of 1 mg/kg/h、0.6–1.2 mg/kg/h and 3.0–6.0 mg/kg/h was given by continuous intravenous infusion to maintain a BIS of 40–60 till the end of the surgery. The incidence rates of body movement, respiratory depression, and adverse effects were compared among the groups.ResultsThe incidence of injection pain was much higher in Group P (64.1%) than that in Group R (3.4%) and Group C (3.2%, both P < 0.001). The onset time was significantly shorter in Group P than that in Group R and Group C (both P < 0.01). The awakening time (MOAA/S score = 3) was longest in Group R, followed by Groups C and Group P (P < 0.01). The time to complete recovery (MOAA/S score = 5) has no significantly difference between Group C and Group P, whereas the onset time was significantly shorter in Group R (P < 0.01). The number of body movements was significantly higher in Group R than that in Group C and Group P (P < 0.01). The incidence of hypotension was significantly lower in Group R than that in Group C and Group P (both P < 0.01). The rate of respiratory inhibition was significantly lower in Group R and Group C than that in Group P (both P < 0.05).ConclusionConsidering jointly the safety and efficacy, ciprofol seems to be the best choice for sedation.